Distribution and prevalence of the myxozoan parasite Tetracapsuloides bryosalmonae in northernmost Europe: analysis of three salmonid species - Lauringson M.; Ozerov M. Y.; Lopez M.-E.; Wennevik V.; Niemelä E.; Vorontsova T. Y.; Vasemägi A. (INTER-RESEARCH, 2025)
Global climate change is altering the abundance and spread of many aquatic parasites and pathogens. Proliferative kidney disease (PKD) of salmonids caused by the myxozoan Tetracapsuloides bryosalmonae is one such emerging disorder, and its impact is expected to increase with rising water temperature. Yet, the distribution and prevalence of T. bryosalmonae in Northern Europe remain poorly characterized. Here, we studied 43 locations in 27 rivers in northernmost Norway and Finland to describe T. bryosalmonae infection frequency and patterns in 1389 juvenile salmonids. T. bryosalmonae was discovered in 12 out of 27 rivers (44{\%}) and prevalence ranged from 4.2 to 55.5{\%} in Atlantic salmon and from 5.8 to 75{\%} in brown trout among infected rivers. In sympatric populations, brown trout was more frequently infected with T. bryosalmonae than was salmon. Age-specific parasite prevalence patterns revealed that in contrast to lower latitudes, the infection of juvenile fish predominantly occurs during the second summer or later. Temperature monitoring over 2 yr indicated that the mean water temperature in June was 2.1 to 3.2{\textdegree}C higher in rivers containing T. bryosalmonae compared to parasite-free rivers, confirming the important role of temperature in parasite occurrence. Temporal comparison in T. bryosalmonae prevalence over a 10 yr period in 11 rivers did not reveal any signs of contemporary parasite spread to previously uninfected rivers. However, the wide distribution of T. bryosalmonae in rivers flowing to the Barents Sea indicates that climate change and heat waves may cause new disease outbreaks in northern regions.